Why Najib is the most interesting politician on Instagram - Mohamed, Shafizan (Malaysiakini, 2018)
LETTER | Hate him or love him, Najib Abdul Razak is the most interesting Malaysian politician to follow on Instagram. With over half a million followers, he may not be the most popular, (that title goes to Dr Mahathir Mahomad who currently has over three million) but he is amongst the most active and most personal.